Numerical study of the influence of surface reaction probabilities on reactive species in an rf atmospheric pressure plasma containing humidity. (8th November 2017) - Schröter, Sandra; Gibson, Andrew R; Kushner, Mark J; Gans, Timo; O'Connell, Deborah
Abstract: The quantification and control of reactive species (RS) in atmospheric pressure plasmas (APPs) is of great interest for their technological applications, in particular in biomedicine. Of key importance in simulating the densities of these species are fundamental data on their production and destruction. In particular, data concerning particle-surface reaction probabilities in APPs are scarce, with most of these probabilities measured in low-pressure systems. In this work, the role of surface reaction probabilities, γ, of reactive neutral species (H, O and OH) on neutral particle densities in a He–H2 O radio-frequency micro APP jet (COST- μ APPJ) are investigated using a global model. It is found that the choice of γ, particularly for low-mass species having large diffusivities, such as H, can change computed species densities significantly. The importance of γ even at elevated pressures offers potential for tailoring the RS composition of atmospheric pressure microplasmas by choosing different wall materials or plasma geometries.